STABILIZATION OF EMULSIONS BY Monodora myristica SEED PROTEIN HYDROLYSATE: EFFECT OF MOLECULAR WEIGHT DISTRIBUTIONS ON SURFACE, EMULSIFYING AND FOAMING PROPERTIES - Samuel, Adeiza Emmanuel; Bwala, Hyeladzira Yusuf (FUDMA Journal of Sciences, 2025)
Development of sustainable benign emulsifiers from bioresource for industrial applications has continued to dominate research frontiers. Therefore, this research aimed to investigate the effect of varied molecular weights of Monodora myristica seed protein on the surface, emulsifying and foaming properties of emulsion systems. M. myristica seed protein was extracted via dialysis and fluxed into > 12, 000 kDa (MPF1), 12, 000-10, 000 kDa (MPF2), 10, 000-8, 000 kDa (MPF3), 8, 000-4, 000 kDa (MPF4) and < 4, 000 kDa (MPF5) molecular weights distributions. The results showed that the lower molecular weights M. myristica seed polypeptides fluxes were more distributed with aliphatic, hydrophilic and polar amino acids, whereas aromatic, hydrophobic, non-polar and sulphur-based amino acids residues were inherently found in the higher molecular weights variant. The surface tension of the amphoteric polypeptides increased with molecular weights, but decreased with protein flux concentration, consistent with their refractive index (1.2835-1.4612) and surface hydrophobicity index (17.55-48.22). The interfacial protein concentration and adsorbed protein, increased with molecular weight distributions of the protein fluxes. The emulsifying stability index (55.38-78.44 min.), average particle size of droplets (63.92-188.50 µm) and protein solubility (58.48-78.44 %), revealed that the higher molecular weights M. myristica seed protein fluxes has a greater tendency to form viscous stable emulsion with reduced foaming properties. The physicochemical properties exhibited by M. myristica seed polypeptide fluxes, were largely influenced by their amino acids residues and molecular weight distributions and present these specialty biopolymers with auspicious potential as suitable emulsifiers in food, pharmaceutical and chemical formulations.
Keywords: Polypetides; Monodora myristica; Emulsifier; Molecular weight; Functional properties